(untitled) (Scientific journal of the Fergana State University, 2024)
In the article, approaches to water security in the Ferghana Valley and its scientific and theoretical aspects, measures for the rational use of water resources, issues of water security and the activities of the international water community are analyzed with the help of materials from scientific literature.